2015
DOI: 10.1371/journal.pone.0139840
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of Morella rubra and Its Relatives (Myricaceae) and Genetic Resources of Chinese Bayberry Using RAD Sequencing

Abstract: Phylogenetic relationships among Chinese species of Morella (Myricaceae) are unresolved. Here, we use restriction site-associated DNA sequencing (RAD-seq) to identify candidate loci that will help in determining phylogenetic relationships among Morella rubra, M. adenophora, M. nana and M. esculenta. Three methods for inferring phylogeny, maximum parsimony (MP), maximum likelihood (ML) and Bayesian concordance, were applied to data sets including as many as 4253 RAD loci with 8360 parsimony informative variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 59 publications
(64 reference statements)
4
16
0
Order By: Relevance
“…Despite the genetic distance among the genera, there were a sufficient number of shared loci recovered between the Zamiaceae and Cycadaceae genera. These results mirror what was found in Myricaceae (Liu et al, ) and Diapensiaceae (Hou et al, ), as they also found a significant drop in loci recovered in more distantly related taxa, indicating that genetic differences between families would be considerable, as we found between Zamiaceae and Cycadaceae.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Despite the genetic distance among the genera, there were a sufficient number of shared loci recovered between the Zamiaceae and Cycadaceae genera. These results mirror what was found in Myricaceae (Liu et al, ) and Diapensiaceae (Hou et al, ), as they also found a significant drop in loci recovered in more distantly related taxa, indicating that genetic differences between families would be considerable, as we found between Zamiaceae and Cycadaceae.…”
Section: Discussionsupporting
confidence: 91%
“…These results mirror what was found in Myricaceae (Liu et al, 2015) and Diapensiaceae (Hou et al, 2015), as they also found a significant drop in loci recovered in more distantly related taxa, indicating that genetic differences between families would be considerable, as we found between Zamiaceae and Cycadaceae.…”
Section: Assembly Of Radseq Datasupporting
confidence: 89%
“…bangwei is the only semi-wild tea plant that has been reported [ 7 ] until now. Despite the relatively small population used in this study, the number of samples was comparable with those used in several molecular phylogenetic research papers focusing on Pedicularis [ 46 ], temperate bamboos [ 47 ] and Chinese bayberry [ 48 ] that used RAD-Seq technology. The methods for the identificaton of SNPs and genotyping were also similar to those used in these papers.…”
Section: Putative Selective Footprints During Tea Domesticationmentioning
confidence: 99%
“…Common to all of these approaches is the initial usage of restriction enzymes and subsequent sequencing of a small section of the genome to reduce the complexity of the target DNA. RAD-Seq, which was developed to identify polymorphic variants in genomic regions adjacent to restriction enzyme digestion sites [ 37 , 42 ], has proven to be particularly suitable for species that lack a published genome sequence [ 43 – 45 ] and has provided genome-scale SNP data that have successfully revealed information for phylogenetic inferences in Pedicularis [ 46 ], temperate bamboos [ 47 ] and Chinese bayberry [ 48 ], population genetics [ 49 – 50 ], species identification [ 51 – 52 ], species evolution [ 53 ] and phylogenomics [ 54 – 55 ]. Additionally, RAD-Seq can also be utilized for association mapping [ 56 ] and genetic mapping [ 42 , 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rapid progress in high-throughput sequencing technologies has provided an opportunity to infer genome-wide information from organisms without reference genomes with affordable cost. Reduced-representation genome sequencing allows us to discover thousands of genetic markers from many samples for population genomics studies 17 – 19 . These methods which consisted of restriction site associated DNA sequencing (RAD-seq) and genotyping by sequencing (GBS) have been successfully applied to population genomics studies of mangy species 20 – 22 .…”
Section: Introductionmentioning
confidence: 99%